2016
DOI: 10.1002/ccd.26696
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous vein graft near‐infrared spectroscopy imaging insights from the lipid core plaque association with clinical events near‐infrared spectroscopy (ORACLE‐NIRS) registry

Abstract: Objectives We sought to examine near-infrared spectroscopy (NIRS) imaging findings of aortocoronary saphenous vein grafts (SVGs). Background SVGs are prone to develop atherosclerosis similar to native coronary arteries. They have received little study using NIRS. Methods We examined the clinical characteristics and imaging findings from 43 patients who underwent NIRS imaging of 45 SVGs at our institution between 2009 and 2016. Results The mean patient age was 67 ± 7 years and 98% were men, with high prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Comparable to native atherosclerosis, hypercholesterolemia, an import driver of VGD and lipid burden, is clearly associated with vein graft age ( 159 ). Analysis of human vein grafts obtained at autopsy has shown that coronary vein grafts undergo rapid atherosclerotic lesion development ( 24 ).…”
Section: Accelerated Atherosclerosis and Late Stage Failurementioning
confidence: 99%
“…Comparable to native atherosclerosis, hypercholesterolemia, an import driver of VGD and lipid burden, is clearly associated with vein graft age ( 159 ). Analysis of human vein grafts obtained at autopsy has shown that coronary vein grafts undergo rapid atherosclerotic lesion development ( 24 ).…”
Section: Accelerated Atherosclerosis and Late Stage Failurementioning
confidence: 99%
“…In a near-infrared spectroscopy imaging study, SVG age was associated with higher lipid core burden index, its only independent predictor, and angiographic stenosis was significantly greater among SVGs aged 5 years and older. 25 In several studies, SVG age was greater in SVGD group versus patent SVG group and was an independent predictor of SVGD 26,27 ; in one study it correlated negatively with stable angina and positively with MHR. 26…”
Section: Discussionmentioning
confidence: 93%
“…In a near-infrared spectroscopy imaging study, SVG age was associated with higher lipid core burden index, its only independent predictor, and angiographic stenosis was significantly greater among SVGs aged 5 years and older. 25 In several studies, SVG age was greater in SVGD group versus patent SVG group and was an independent predictor of SVGD 26,27 ; in one study it correlated negatively with stable angina and positively with MHR. 26 In the present primary cohort, patients with acute coronary syndrome after CABG had worse NYHA class and greater LVEDD than patients with stable angina pectoris (p = .005 and p = .0002, respectively), and acute coronary syndrome after CABG was an independent multivariate predictor of SVGD.…”
Section: Many Predisposing Factors Have Been Associatedmentioning
confidence: 94%
“…It needs to be highlighted that only periprocedural lipid plasma levels were measured with no insight into long-term analysis. Danek et al [ 40 ] studied the progression of atherosclerosis in saphenous vein grafts and revealed that in contrast to the LDL-C and TG measured annually, the periprocedural measurements showed no association with max LCBI 4mm . It was also found that annual measurements are more representative for the assessment of plaque morphology.…”
Section: Discussionmentioning
confidence: 99%